Pesticide residues in bee pollen - validation of the gas chromatography-mass spectrometry multiresidual method and a survey of bee pollens from Slovenia - Helena BAŠA ČESNIK (University of Ljubljana, Biotechnical Faculty, 2021)
A new analytical method for determining environmental pesticide residues in pollen was introduced and validated. The extraction was conducted using acetonitrile, the clean-up using Supelclean Ultra 2400 solid phase extraction cartridges, which contain Grapsphere, anion exchanger, C18 and zirconia-based sorbent, and the determination was conducted using gas chromatography coupled with mass spectrometry. The method was applied in practice. A total of 49 active substances (pesticides) were sought in 30 bee pollen samples gathered from Slovenian beekeepers from all 12 statistical regions of Slovenia. The fungicide azoxystrobin was the only active substance found and was found only in one sample with a concentration of < 0.05 mg kg-1. The active substances sought were not detected in 96.7 % of the samples analysed. The risk assessment revealed that the analysed pollen samples do not represent an unacceptable risk for consumers. The results were compared with those from the literature and the outcome was that bee pollen from Slovenia contained a lower number of active substances at mainly lower contents as compared pollen from some other European countries.